2010
DOI: 10.1007/s00421-010-1732-z
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of haemoglobin mass to increases in cycling performance induced by simulated LHTL

Abstract: We sought to determine whether improved cycling performance following 'Live High-Train Low' (LHTL) occurs if increases in haemoglobin mass (Hb(mass)) are prevented via periodic phlebotomy during hypoxic exposure. Eleven, highly trained, female cyclists completed 26 nights of simulated LHTL (16 h day(-1), 3000 m). Hb(mass) was determined in quadruplicate before LHTL and in duplicate weekly thereafter. After 14 nights, cyclists were pair-matched, based on their Hb(mass) response (ΔHb(mass)) from baseline, to for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
46
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 45 publications
7
46
1
Order By: Relevance
“…Our findings are in contrast to the results of the initial LHTL study (34) and several follow-up studies, where improvements in VO 2 max (7,16,50,57) or endurance performance (57,59) have been reported. This is intriguing, since we designed the LHTL intervention according to generally accepted recommendations, which for simulated altitude, range from 4 wk at 2,500 -3,000 m (12-16 h/day) (61) to 18 days at 2,500 m (12 h/day) (44).…”
Section: Impact Of Lhtl On Aerobic Performancecontrasting
confidence: 56%
“…Our findings are in contrast to the results of the initial LHTL study (34) and several follow-up studies, where improvements in VO 2 max (7,16,50,57) or endurance performance (57,59) have been reported. This is intriguing, since we designed the LHTL intervention according to generally accepted recommendations, which for simulated altitude, range from 4 wk at 2,500 -3,000 m (12-16 h/day) (61) to 18 days at 2,500 m (12 h/day) (44).…”
Section: Impact Of Lhtl On Aerobic Performancecontrasting
confidence: 56%
“…Changes in Hb mass induced by accelerated erythropoiesis (as in the case of altitude training, rhEPO use [45]) can be observed in as little as 10 d (14,19), which indicates that a minimum threshold for iron stores must be reached before erythropoiesis is ''switched on.'' The flood of iron into the system via the IV route may therefore be sufficient to activate the erythropoietic system, whereas 6 wk of oral supplementation was not sufficient to reach this threshold.…”
Section: Discussionmentioning
confidence: 98%
“…This has previously been shown in a study by Manzi et al 6 with eight recreational long-distance runners. These authors reported that speed at 2 mmol·L Even though internal training load methods such as bTRIMP 10 , Lucia's TRIMP (luTRIMP) 5 and session-RPE (sRPE) 11 and external training load methods such as Training Stress Score™ (TSS) 12 are mentioned in the literature, there is little evidence of a doseresponse relationship between these measures and training outcomes. Other measures of training load such as Edwards' TRIMP (eTRIMP) and iTRIMP have been applied in other sports but not in cycling.…”
Section: Introductionmentioning
confidence: 99%